Cerebral ischemia-induced angiogenesis is dependent on tumor necrosis factor receptor 1-mediated upregulation of α5β1 and αVβ3 integrins - Huang, Heng; Huang, Qijuan; Wang, Fuxin; Milner, Richard; Li, Longxuan (Journal of neuroinflammation, 2016)
The pro-inflammatory cytokine, tumor necrosis factor-α (TNF-α), is expressed in ischemic tissue and is known to modulate angiogenesis; however, the role of the two distinct TNF-α receptors, TNFR1 and TNFR2, in mediating angiogenic signaling after cerebral ischemic stroke is relatively unknown. C57BL6 mice were subject to 90 min of ischemia by temporary occlusion of the middle cerebral artery (MCAO) and given daily intra-cerebroventricular injections of antibodies against TNFR1, TNFR2 or control IgG (doses of 10, 50, and 100 ng/day) for 4 days following 90 min MCAO. Vascular remodeling and α5β1 and αVβ3 integrin expression were then examined in the brains of these mice after 4, 7, and 14 days post-ischemia. In parallel in vitro studies, flow cytometry was used to determine the influence of TNF-α on proliferation and integrin expression of human brain microvascular endothelial cells (HBMECs). The post-ischemic cerebral angiogenic response was inhibited by antibodies against TNFR1 but not TNFR2, and this correlated with reduced endothelial proliferation and decreased α5β1 and αVβ3 integrin expression after 4 and 7 days post-ischemia. Consistent with these findings, in vitro studies showed that TNF-α induced endothelial proliferation and upregulation of α5β1 and αVβ3 integrins was abrogated by anti-TNFR1 but not anti-TNFR2 antibodies in cultured HBMECs. In addition, blocking antibodies to α5β1 and αVβ3 integrins significantly inhibited TNF-α-induced HBMEC proliferation. Our results suggest that TNFR1-mediated signaling plays a critical role in triggering angiogenic integrins and subsequent angiogenic responses following cerebral ischemia. These novel findings could form a platform for future therapeutic strategies aimed at stimulating angiogenesis following cerebral ischemia.